High-Concentration Solvent Exfoliation of Graphene. - COLEMAN, JONATHAN NESBIT; LOTYA, MUSTAFA (Wiley-Blackwell, 2010)
We demonstrate a method to prepare graphene dispersions at high concentrations, up to 1.2 mg/ml, with yields of up to 4wt% monolayers. This process relies on low-power sonication for long times, up to 460 hours. TEM shows the sonication to reduce the flake size with flake dimensions scaling as t-1/2. However, the mean flake length remains above 1 mm for all sonication times studied. Raman spectroscopy shows defects are introduced by the sonication process. However, detailed analysis suggests that predominately edge rather then basal-plane defects are introduced. We have used these dispersions to prepare high quality free-standing graphene films. The dispersions can be heavily diluted by water without sedimentation or aggregation. This method facilitates graphene processing for a range of applications.
PUBLISHED
Keywords: Physics; graphene